Floriculture on the farm - Secrest, May (My University, 1892)
Introduction: Everyone enjoys a ride through the country when the weather is pleasant and the roads are smooth and firm. You delight in the easy movement through green lanes with flowers blossoming by the wayside, birds singing in the hedges, through which you catch glimpses of meadows, pastures, and fields of grain; and above you the blue sky with fleecy white clouds sailing across it. And yet there is something monotonous in the drive. What is it? It is not Nature’s work but man’s work, -- the lovely dreary farm house after farm house that you pass as you journey on. Some of the houses stand out boldly against the sky with nothing to relieve the sharp outlines. In other cases a forlorn half-hearted attempt has been made to improve the surroundings. Perhaps there is a love broken tree in the fence corner, a few stalks of tiger lilies in a bed with stones set on end for a border, but between which the hews are now taking a dust bath. A straggling rose bush or two may be seen in the foreground, but weeds and tall rank grass are the prime rulers here, while pigs, pig-pens, and stables also bear a prominent place in the foreground.
Citation: Secrest, May. Floriculture on the farm. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Floriculture; Agriculture; Botany; Farm; Theses; Manuscripts (documents)